Trends in inequalities in premature cancer mortality by educational level in Colombia, 1998–2007 (2015)
ABSTRACT: Background: There is a paucity of studies on socioeconomic inequalities in cancer mortality in developing countries. We examined trends in inequalities in cancer mortality by educational attainment in Colombia during a period of epidemiological transition and rapid expansion of health insurance coverage. Methods: Population mortality data (1998-2007) were linked to census data to obtain age-standardised cancer mortality rates by educational attainment at ages 25-64 years for stomach, cervical, prostate, lung, colorectal, breast and other cancers. We used Poisson regression to model mortality by educational attainment and estimated the contribution of specific cancers to the slope index of inequality in cancer mortality. Results: We observed large educational inequalities in cancer mortality, particularly for cancer of the cervix (rate ratio (RR) primary vs tertiary groups=5.75, contributing 51% of cancer inequalities), stomach (RR=2.56 for males, contributing 49% of total cancer inequalities and RR=1.98 for females, contributing 14% to total cancer inequalities) and lung (RR=1.64 for males contributing 17% of total cancer inequalities and 1.32 for females contributing 5% to total cancer inequalities). Total cancer mortality rates declined faster among those with higher education, with the exception of mortality from cervical cancer, which declined more rapidly in the lower educational groups. Conclusions: There are large socioeconomic inequalities in preventable cancer mortality in Colombia, which underscore the need for intensifying prevention efforts. Reduction of cervical cancer can be achieved through reducing human papilloma virus infection, early detection and improved access to treatment of preneoplastic lesions. Reinforcing antitobacco measures may be particularly important to curb inequalities in cancer mortality.